Innovation In Islamic Educational Administration: Integrating Islamic Values And Modern Management - Ilwan, Ilwan; Ali, Faisal; Fakri, Fakri (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Abstrak Penelitian ini membahas inovasi administrasi pendidikan Islam yang menekankan integrasi nilai-nilai dasar Islam dengan pendekatan manajemen modern. Tujuan utama penelitian adalah menganalisis peran inovasi dalam meningkatkan efektivitas administrasi pendidikan Islam, khususnya pada komponen kurikulum, tenaga pendidik, metode pembelajaran, serta sarana prasarana. Metode penelitian yang digunakan adalah penelitian kepustakaan dengan pendekatan kualitatif, menggunakan sumber berupa buku, artikel jurnal, dan dokumen akademik yang relevan. Hasil penelitian menunjukkan bahwa kepala sekolah atau madrasah sebagai administrator memiliki peran sentral dalam menciptakan inovasi manajerial yang kreatif, adaptif, dan kritis terhadap perubahan. Implementasi inovasi terbukti meningkatkan kualitas layanan pendidikan, memperkuat organisasi sekolah, serta mengoptimalkan pemanfaatan teknologi dalam pembelajaran dan manajemen. Kesimpulan penelitian menegaskan bahwa inovasi administrasi pendidikan Islam merupakan strategi penting untuk mewujudkan lembaga pendidikan yang unggul, adaptif terhadap perkembangan zaman, sekaligus tetap berlandaskan nilai-nilai Islam. Kata Kunci: Inovasi, Administrasi Pendidikan Islam, Manajemen Modern, Kepala Sekolah, Mutu Pendidikan Abstract This study explores innovation in Islamic educational administration, focusing on the integration of fundamental Islamic values with modern management approaches. The main objective is to examine the role of innovation in enhancing the effectiveness of Islamic educational administration, particularly in curriculum development, teacher professionalism, learning methods, and educational facilities. The study employed a qualitative library research method, drawing on books, journal articles, and relevant academic documents. The findings reveal that school or madrasah principals, as administrators, play a central role in fostering managerial innovation that is creative, adaptive, and responsive to change. The implementation of innovation has been shown to improve the quality of educational services, strengthen institutional organization, and optimize the use of technology in both teaching and management. The study concludes that innovation in Islamic educational administration is a crucial strategy for establishing high-performing educational institutions that remain adaptive to contemporary challenges while firmly grounded in Islamic values. Keywords: Innovation, Islamic Educational Administration, Modern Management, School Principal, Educational Quality